Biodegradation of Polychlorinated Dibenzo‐p‐Dioxins by Pseudomonas mendocina Strain NSYSU. Issue 1 (1st January 2014) - Lin, W. C.; Chang‐Chien, G. P.; Kao, C. M.; Newman, L.; Wong, T. Y.; Liu, J. K.
Abstract : The dioxin‐degrading bacterium Pseudomonas mendocina strain NSYSU (NSYSU strain) has been isolated from dioxin‐contaminated soil by selective enrichment techniques. In the present study, the NSYSU strain was investigated for its capability to biodegrade polychlorinated dibenzo‐ p ‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) under aerobic and anaerobic conditions. High‐resolution gas chromatography–mass spectrometry and a chemically activated luciferase gene expression bioassay were performed to determine the presence of dioxin compounds. The results indicate that the NSYSU strain could degrade PCDDs and PCDFs under anaerobic conditions in liquid cultures. The main intermediates of the dechlorination process were identified. The results of the bioreactor test indicate that the NSYSU strain could also degrade PCDDs and PCDFs effectively in soil slurries under aerobic conditions. Results from the bioreactor experiment show that approximately 98 and 97% of octachlorodibenzofuran and OCDD were degraded, respectively. The dioxin concentrations in soil slurry decreased from 5823 to 1198 pg toxic equivalency g −1, resulting in total dioxin removal of 79%. These first findings suggest that the NSYSU strain has the potential to be an effective tool for the bioremediation of soils contaminated with highly recalcitrant organic compounds.